If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-12(n+10)+n=9n-8(n-9)
We move all terms to the left:
-12(n+10)+n-(9n-8(n-9))=0
We add all the numbers together, and all the variables
n-12(n+10)-(9n-8(n-9))=0
We multiply parentheses
n-12n-(9n-8(n-9))-120=0
We calculate terms in parentheses: -(9n-8(n-9)), so:We add all the numbers together, and all the variables
9n-8(n-9)
We multiply parentheses
9n-8n+72
We add all the numbers together, and all the variables
n+72
Back to the equation:
-(n+72)
-11n-(n+72)-120=0
We get rid of parentheses
-11n-n-72-120=0
We add all the numbers together, and all the variables
-12n-192=0
We move all terms containing n to the left, all other terms to the right
-12n=192
n=192/-12
n=-16
| -14=1+n-6n | | -5(1+6n)=-185 | | 50x+14,040=20x+12,500 | | 10−6p=3p−5. | | -7(2-8b)=-238 | | 8x-16=76 | | 50x+14,040=12,500+20x | | 24=20+10x | | -11(x-14)=-77 | | -10-3(-4+6r)=-3+5(1+6r) | | -150=3(6p-8) | | 4=0.84x | | -11(x-12)=-75 | | y-4+2=3 | | |4-(2x/5)|=18 | | -11(x-14)=-75 | | 1-3p=-6+6p-8p | | 25(12y+20)−45=920(2y−1) | | 11(x-3)-1=7(x-6) | | 12z=4 | | -6p+4(6-6p)=264 | | x+.5x=50 | | x^2=36/8` | | `2=1.015^x | | 5(y+2)=6(y+6) | | 93.6=9(m+22) | | 7y+2(y+2)=-6 | | 4(3a+4)=88 | | y=2(-3)2-3(-3)-2 | | 1/4m-6=12 | | 16-27=t+9+4t | | 6-2x=4x+12 |